2017
DOI: 10.1111/sum.12324
|View full text |Cite
|
Sign up to set email alerts
|

The influence of compost and zeolite co‐addition on the nutrients status and plant growth in intensively cultivated Mediterranean soils

Abstract: The main objective of the study was to test the benefits of compost and zeolite co-addition on the fertility of organic-rich Mediterranean soils. Previous pot study in greenhouse found that zeolites mixed with compost significantly improved potassium availability as well as exchangeable potassium capacity in the soils. To further test this finding, a field experiment was conducted using potatoSolanum tuberosum L., desiree cultivar in peat soils of the Hula Valley, Israel. Adhering to the protocol of the greenh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
27
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 29 publications
8
27
1
Order By: Relevance
“…According to Ghannad et al [20] who studied the effect of different fertilizer programs on the quality and yield of potato, it was found that zeolite treatment as a fertilizer management practice increased the crop yield. Another suggested farming practice includes the combination of zeolite and compost which presents several advantages such as the improvement of water use efficiency and of soil properties, the increase of soil water holding capacity, and the reduction of soil and environmental pollution [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…According to Ghannad et al [20] who studied the effect of different fertilizer programs on the quality and yield of potato, it was found that zeolite treatment as a fertilizer management practice increased the crop yield. Another suggested farming practice includes the combination of zeolite and compost which presents several advantages such as the improvement of water use efficiency and of soil properties, the increase of soil water holding capacity, and the reduction of soil and environmental pollution [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [35], who studied zeolite as a slow release fertilizer in spinach cultivation, reported that zeolite treatment increased crop yield over the conventional fertilizer. Moreover, farming practices that include combinatory applications of zeolite and composts may present various benefits, including an increase in water use efficiency and the improvement of soil properties and water holding capacity, while they may also help towards the reduction of soil degradation and the pollution of the environment [36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Peat amendments have also been observed to increase the rate of soil N supply in oil sands mine soils (Pinno et al, ). In our study, the organic biosolids had relatively higher organic matter and nutrient concentrations (Table ), which could have directly improved the soil nutrient status (Adebayo et al, ; Jόzefowska et al, ; Litaor et al, ). Additions of organic biosolids to postmined soils have been suggested to restore other soil properties (e.g., soil porosity and density, soil pH, and microbial growth) (Asensio et al, ; Escobar & Hue, ; Zornoza et al, ), thus enhancing the nutrient status of mine‐tailing soils.…”
Section: Discussionmentioning
confidence: 53%
“…In many cases, low soil fertility is the limiting factor for plant growth in postmined soils (Arocena, Mourik, Schilder, & Cano, ; Daws, Standish, Koch, & Morald, ). Thus, increasing soil nutrients after organic amendment has been widely reported to improve plant growth (Litaor et al, ; Pinno et al, ). In addition, manure amendments were found to increase the ratios of aboveground biomass to root biomass, indicating higher availability of soil nutrients, which may have resulted in less biomass allocation to roots by plants (Davidson, ; Ericsson, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation